The handbook of dispute resolution - Moffitt, Michael L. 1968-; Bordone, Robert C. 1972- (Jossey-Bass, 2005)
This volume is an essential, cutting-edge reference for all practitioners, students, and teachers in the field of dispute resolution. Each chapter was written specifically for this collection and has never before been published. The contributors--drawn from a wide range of academic disciplines--contains many of the most prominent names in dispute resolution today, including Frank E. A. Sander, Carrie Menkel-Meadow, Bruce Patton, Lawrence Susskind, Ethan Katsh, Deborah Kolb, and Max Bazerman. The Handbook of Dispute Resolution contains the most current thinking about dispute resolution. It synthesizes more than thirty years of research into cogent, practitioner-focused chapters that assume no previous background in the field. At the same time, the book offers path-breaking research and theory that will interest those who have been immersed in the study or practice of dispute resolution for years. The Handbook also offers insights on how to understand disputants. It explores how personality factors, emotions, concerns about identity, relationship dynamics, and perceptions contribute to the escalation of disputes. The volume also explains some of the lessons available from viewing disputes through the lens of gender and cultural differences.